Study of socio-demographic patterns and epidemiological correlates of unintentional injuries among 1-5 year children in Moradabad - Yadav, Sachin Singh; Shrivastava, Anurag; Mishra, Prabhaker; Prabhakar, Anish (International Journal Of Community Medicine And Public Health, 2017)
Background: Unintentional injuries among children are an emerging public health problem. Accidental injuries are one of the leading causes of death, hospitalization and disability across the world. Fragile, helpless and innocent, an infant enters the world completely dependent on its caretakers. Children’s environment plays a critical role, both in the occurrence and severity of an injury. Hence, this study was carried out to assess the domestic unintentional injuries among under-five children. Methods: This cross-sectional study was undertaken in the urban field practice area of Teerthanker Mahaveer Medical College and Research Centre Moradabad. Information about domestic accidents among the family members in the last one year from the date of survey was obtained by interviewing the head of the family or responsible member of the family age ≥ 18 year. Study target sample size was taken 440 was selected by using two stage cluster sampling technique. Results: Out of 440 children 20% (88) reported to have experience unintentional injuries. History of fall was the commonest 42 (47.3%) form of injury reported followed by injury due to sharp object and road traffic accident. Toddlers, male child were affected more. Only 48.9% caregivers were aware about first aid measures to be taken after unintentional injury, 71.3% participants reported implementation of preventive measures. Conclusions: Unintentional injuries are becoming more common. We recommend for prompt and target group interventions in order to prevent and control the domestic accidents, promotion of household safety measures and creation of awareness among the community using information, education, and communication (IEC) interventions have to be undertaken.